The Monotone Robin-Robin Domain Decomposition Methods for the Elliptic Problems with Stefan-Boltzmann Conditions (Communications in Computational Physics, 2010)
This paper is concerned with the elliptic problems with nonlinear Stefan-Boltzmannboundary condition. By combining with the monotone method, the Robin-Robindomain decomposition methods are proposed to decouple the nonlinear interfaceand boundary condition. The monotone properties are verified for both the multiplicativeand the additive domain decomposition methods. The numerical resultsconfirm the theoretical analysis.